Weed control in angelica (Angelica archangelica L.) - Lazarević, Jovan; Vrbnicanin, Sava; Dragumilo, Ana; Markovic, Tatjana; Savic, Aleksandra; Bozic, Dragana (Acta herbologica, 2021)
Plantation cultivation of medicinal plants is expanding, and since weed control is the biggest challenge in this production, the aim of the study was to examine the possibility of their control by mulching. In addition, the herbicide metamitron (Metak 700 SC, 700 g active substance L-1; Galenika Phytopharmacy) was included in the research, the use of which in such crops is acceptable in some countries. Angelica archangelica L.was chosen as the experimental crop, whose essential oil from the root is one of the most appreciated on the market, so an increase in production areas can be expected. The experiment was set up in Kujavica (Vladimirci municipality) in five treatments (completely random block system in four replications), as follows: agrotextile waterproof foil, sawdust (mixture of acacia and oak wood; layer thickness - 10 cm), herbicide metamitron (split application: 1050 + 1050 g a.s. ha-1), positive (regularly weeded) and negative (weeded) control. During the season, the number of weeds per m² and height were assessed three times, and after the third assessment, fresh aboveground biomass was measured. Data analysis was performed in the software package STATISTICA 7.0 using one - factor analysis of variance and Duncan's test.The highest weediness was recorded in the negative control, and the most common were grass species such as Setaria viridis (L.) P. B. (12,5 plants m-2), Sorghum halepense (L.) Pers. (8 plants m-2), Cynodon dactylon (L.) Pers. (3,75 plants m-2), etc. A high level of weeding was also found in the treatment with the herbicide metamitron, where the dominant grass species were also: S. viridis (24,75 plants m-2), Echinochloa crus – galii (L.) P. Beauv. (8,95 plants m-2), C. dactylon (2,3 plants m-2). Sawdust mulch resulted in a reduction in weediness compared to the previous two treatments. The dominant species in this treatment were: S. viridis (8 plants m-2), S. halepense (4,5 plants m-2) and Ambrosia artemisiifolia L. (1,13 plants m-2). Mulch foil and regular weeding control were free of weeds. Thus, the best efficiency in weed control was achieved by applying agrotextile mulch foil, which completely prevented weed germination (efficiency 100%), a much weaker effect was achieved by using sawdust (efficiency 51,28%), while metamitron reduced fresh weed biomass by only 26,71%. The obtained results show that mulching as a physical method of weed control in angelica crop is more suitable in comparison with the application of the herbicide metamitron if the crop is dominated by grass species, which are not in the spectrum of action of this herbicide. The significance of these results is so great that in our country metamitron, as well as other herbicides, is not registered for use in medicinal plants.
Keywords: Angelica archangelica L., agrotextile mulch foil, sawdust, metamitron